2004
DOI: 10.1074/jbc.m309535200
|View full text |Cite
|
Sign up to set email alerts
|

Pro-nucleotide Inhibitors of Adenylyl Cyclases in Intact Cells

Abstract: 9-Substituted adenine derivatives with protected phosphoryl groups were synthesized and tested as inhibitors of adenylyl cyclase in isolated enzyme and intact cell systems. Protected 3-phosphoryl derivatives of 2,5-dideoxyadenosine (2,5-dd-Ado) and ␤-L-2,5-ddAdo, protected 5-phosphoryl derivatives of ␤-L-2,3-ddAdo, and protected phosphoryl derivatives of two 9-(2-phosphonomethoxy-acyl)-adenines were synthesized. Protection was afforded by two cyclosaligenyl-or three S-acyl-2-thioethyl-substituents. These pro-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…Membrane-permeable Membrane Adenylyl Cyclase Inhibitors. The issues with impermeability of the plasma membrane for nucleotides can be avoided by applying membrane-permeable nucleotide prodrugs (Laux et al, 2004), but this strategy has not yet found broad application in the field, leaving many of the most potent AC inhibitors with little cellular utility. As an alternative strategy, membrane-permeable and hence lipophilic nucleoside analogs can be used in intact cell studies.…”
Section: +mentioning
confidence: 99%
“…Membrane-permeable Membrane Adenylyl Cyclase Inhibitors. The issues with impermeability of the plasma membrane for nucleotides can be avoided by applying membrane-permeable nucleotide prodrugs (Laux et al, 2004), but this strategy has not yet found broad application in the field, leaving many of the most potent AC inhibitors with little cellular utility. As an alternative strategy, membrane-permeable and hence lipophilic nucleoside analogs can be used in intact cell studies.…”
Section: +mentioning
confidence: 99%
“…Our data clearly show that the future design of competitive AC inhibitors should not be limited to adenine nucleotides (30) but should also include guanine, hypoxanthine, and uracil nucleotides. By analogy to P-site inhibitors (85), prodrugs of the competitive AC inhibitors described in this study may become valuable tools for the analysis of the function of specific AC isoforms in intact cells. It is also promising to develop P-site inhibitors with a polyphosphate chain at the 3Ј-O-ribosyl position but bases other than adenine (24,25,28,83).…”
Section: Enzyme Kinetics Of Cyclases and Inhibition Of Cyclases By Mamentioning
confidence: 99%
“…By analogy to antiviral drugs, lipophilic nucleotide prodrugs with high bioavailability have to be designed. Conversion of the nucleotide prodrug to the active nucleoside 5Ј-triphosphate by phosphorylation is then accomplished by specific kinases (Laux et al, 2004). It is noteworthy that MANTNTPs and the corresponding MANT-NTP␥Ss possess comparable potencies on heart AC.…”
mentioning
confidence: 99%